Late-Life Vascular Risk Factors and Alzheimer Disease Neuropathology in Individuals with Normal Cognition. Issue 10 (October 2016) - Besser, Lilah M.; Alosco, Michael L.; Ramirez Gomez, Liliana; Zhou, Xiao-Hua; McKee, Ann C.; Stern, Robert A.; Gunstad, John; Schneider, Julie A.; Chui, Helena; Kukull, Walter A.
Abstract : Vascular risk factors (VRFs) have been associated with clinically diagnosed Alzheimer disease (AD), but few studies have examined the association between VRF and AD neuropathology (ADNP) in cognitively normal individuals. We used longitudinal data from the National Alzheimer's Disease Center's Uniform Data Set and Neuropathology Data Set to examine the association between VRF and ADNP (moderate to frequent neuritic plaques; Braak stage III–VI) in those with normal cognition. Our sample included 53 participants with ADNP and 140 without ADNP. Body mass index (BMI), resting heart rate (HR), and pulse pressure (PP) were measured at each visit; values were averaged across participant visits and examined annual change in BMI, PP, and HR. Hypertension, diabetes, and hypercholesterolemia were self-reported. In the multivariable logistic regression analyses, average BMI and HR were associated with lower odds of ADNP, and annual increases in HR and BMI were associated with higher odds of ADNP. A previously experienced decline in BMI or HR in late-life (therefore, currently low BMI and low HR) as well as a late-life increase in BMI and HR may indicate underlying AD pathology. Additional clinicopathological research is needed to elucidate the role of changes in late-life VRF and AD pathogenesis.